Electrophoretic Banding Pattern Of Esterase Isozyme In Different Tissues Of Puntius Sophore (Cyprinidae : Cypriniformes) - Jahan, Hawa; Gope, Partha Sarathi; Alam, Mohammad Shamimul; Shahjahan, Reza Md (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Esterase isozyme of different tissues of Puntius sophore was analyzed using 7.5 % polyacrylamide gel electrophoresis (PAGE). Fish specimens were collected from local market. The tissues used were taken from different muscles, stomach, fore-, mid- and hind-gut, liver, eyes, gill, heart, kidney, fore-, mid- and hind- brain, eggs and ovary. Six different esterase bands were detected, named Est-1, Est-2, Est-3, Est-4, Est-5 and Est-6 and their relative mobility were 1.0, 0.84, 0.62, 0.33, 0.26 and 0.13 respectively, each of them representing a single allele. The highest esterase activity was found in liver, followed by gill, kidney, heart, brain, intestine, stomach, eye, reproductive organ and skeletal muscles as detected in the staining intensity. Staining intensity of Est-4 and Est-5 was higher and Est-6 was the least stained in all the tissues. Asiat. Soc. Bangladesh, Sci. 42(2): 201-208, December 2016